Nilai-Nilai Pendidikan Islam dalam al qur'an (Kajian Surat Albaqarah Ayat 31-33) - Mari'atul Qiftiyah (Fakultas Agama Islam UMY, 2014)
Nilai-Nilai Pendidikan Islam dalam al qur'an (Kajian Surat Albaqarah Ayat 31-33)